Chapter Македонский esse-перфект: лексическая дистрибуция и контекстные ограничения - Escher, Anastasia (Biblioteca di Studi Slavistici, 2023)
Esse-perfect in Macedonian: lexical distribution and contextual restrictions - The present article deals with the esse-perfect in Macedonian, also found in Aromanian and some Albanian dialects, which is formed with verbs of both aspects by means of the auxiliary sum 'to be' plus the (formally) passive participle. In contrast to previous work on this topic, our research sets out to determine the domains of usage for this construction in Macedonian, both in the standard language and its dialects, especially those on the western periphery and in linguistic enclaves surrounded by Albanian-speaking communities. In addition to personal fieldwork, three main corpora serve as a material basis for this task; see the list of sources at the end of the article. The formation of the esse-perfect is rather limited when compared with the other two perfects of Macedonian. In particular, its distribution clearly depends on lexical verb classes, with language contact accounting for less rigid restrictions and a wider usage of this construction.